Corporate Social Performance, Financial Performance for Firms that Restate Earnings (Issues in Social and Environmental Accounting (ISEA), 2008)
This study examines corporate social performance (CSP) in firms that restate their financial statements and, using a match pair design, compares their performance to firms that do not restate their financial statements.  Utilizing a randomized block design (two years prior to the restatement and two years after the restatement) for a sample of 44 U.S. firms, we found that CSP Strengths, CSP Weaknesses, CSP People Strengths, and CSP People Weaknesses all increased after restatement though weaknesses increased at a greater rate than strengths.  Additionally, using panel data and a match pair design we found, we found that restating firms had a greater increase in CSP Strengths, CSP Weaknesses, CSP Product Strengths, CSP People Strengths and a greater decrease in Total CSP People than non-restating firms after the restatement period.  When comparing the relationships between CSP and financial performance (FP), we found that the positive relationship between ROA and CSP Strengths is greater for restatement firms than non-restating firms.  In particular, we find that this positive relationship is a result of the People dimension of CSP, in particular CSP People Strengths.